Measurement of the longitudinal diffusion of ionization electrons in the MicroBooNE detector - Abratenko, P; An, R; Anthony, J; Asaadi, J; Ashkenazi, A; Balasubramanian, S; Baller, B; Barnes, C; Barr, G; Basque, V; Bathe-Peters, L; Rodrigues, OB; et al. (IOP Science, 2021)
Accurate knowledge of electron transport properties is vital to understanding the information provided by liquid argon time projection chambers (LArTPCs). Ionization electron drift-lifetime, local electric field distortions caused by positive ion accumulation, and electron diffusion can all significantly impact the measured signal waveforms. This paper presents a measurement of the effective longitudinal electron diffusion coefficient, DL, in MicroBooNE at the nominal electric field strength of 273.9 V/cm. Historically, this measurement has been made in LArTPC prototype detectors. This represents the first measurement in a large-scale (85 tonne active volume) LArTPC operating in a neutrino beam. This is the largest dataset ever used for this measurement. Using a sample of ∼70,000 through-going cosmic ray muon tracks tagged with MicroBooNE's cosmic ray tagger system, we measure DL = 3.74+0.28-0.29 cm2/s.